Functional outcomes of percutaneous correction of hallux valgus in not symptomatic flatfoot: a case series study - Catani, Ottorino; Fusini, Federico; Zanchini, Fabio; Sergio, Fabrizio; Cautiero, Giovanni; Villafañe, Jorge Hector; Langella, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Hallux valgus (HV) and Pes Planus (PP) are two common conditions characterized by aesthetic dissatisfaction with or without pain. The aim of the study was to assess clinical and functional outcomes at two years follow-up of percutaneous surgery in patients with HV and concomitant not-symptomatic PP. From January 2014 to May 2015 a total of 12 females and 2 males (14 feet) were enrolled in the study (mean age 41.9±13.28). The inclusion criteria were patients with HV surgically treated with the percutaneous approach, mild or moderate not symptomatic PP at 24 months follow-up. Percutaneous distal metatarsal osteotomy and exostectomy is performed for all patients and followed by a weekly bandage. American Orthopaedic Foot and Ankle Society (AOFAS) score for HV (AOFAS-HV), patient satisfaction, and preoperative and postoperative X-ray at 6 weeks follow-up were evaluated. Numerical data are reported as the mean± SD and 95% confidence intervals. The pre-operative hallux valgus angle (HVA) was 30.14°±11.26°, the post-operative HVA was 18.36°±10.13 with a mean correction of 11.79°±2.67° with p<0.0001. Mean AOFAS-HV increased from 42.07±10.82 pre-operatively to 83±8.96 post-operatively with p<0.0001. One out of 14 patients had recurrence of HV without needing revision surgery at the last follow-up. All patients were satisfied with the clinical outcomes. Our results suggested that percutaneous osteotomy with the mini-burr is an effective treatment for patients with HV despite PP presence, even if the mean functional score was slightly worse when compared with the literature.